Tutor of Resilience: A Model for Psychosocial Care Following Experiences of Adversity - Giordano, Francesca; Cipolla, Alessandra; Ungar, Michael (Frontiers in Psychiatry, 2021)
This article describes a model for training service providers to provide interventions that build resilience among individuals who have experienced adversity. The Tutor of Resilience model emphasizes two distinct dimensions to training: (1) transforming service providers’ perceptions of intervention beneficiaries by highlighting their strengths and capacity for healing; and (2) flexibly building contextually and culturally specific interventions through a five-phase model of program development and implementation. Tutor of Resilience has been employed successfully with child and youth populations under stress in humanitarian settings where mental health and psychosocial support professionals are required to design and deliver interventions that enhance resilience among vulnerable children.